On the Mechanism of Plasmin-induced Aggregation of Human Platelets: Implication of Secreted von Willebrand Factor - Rabhi-Sabile, S.; de Romeuf, C.; Pidard, D. (Thrombosis and Haemostasis, 1998)
Plasmin triggers a strong metabolic activation in human platelets, leading to shape change and granule exocytosis. However, its capacity to induce cell aggregation remains discussed and, when observed, this aggregation is preceded by a remarkable lag phase. We have thus investigated the effect of plasmin on the adhesive proteins which can be secreted by isolated platelets and mediate cell-to-cell interactions, but are also substrates for the enzyme. Immunoblot analysis of fibrinogen (Fg), thrombospondin-1 (TSP-1), fibronectin (Fn) and von Willebrand factor (vWf) was performed on extracts of platelets exposed under stirring to increasing concentrations of plasmin for up to 10 min at 37° C. Under conditions leading to formation of large aggregates, Fg, Fn and TSP-1 are extensively degraded concomitantly with their secretion, and readily lost from the surface of aggregated cells. Part of the monomers in the platelet vWf are cleaved during secretion into two main fragments with Mr ≈180,000 and ≈145,000. However, multimer distribution analysis shows only a slight decrease in the very high molecular weight multimers, and most of the fragmented as well as intact vWf remains associated with the platelet surface when aggregation is maximal. That indeed vWf largely supports plasmin-induced aggregation is suggested by the observation that platelets from a patient with type 3 von Willebrand’s disease, who totally lacks vWf, show little aggregation in response to the enzyme. Finally, plasmin-induced aggregation can be totally inhibited by antagonists of the αIIbβ3 integrin. The present study thus indicates a major role for secreted vWf in platelet aggregation induced by plasmin, through its likely interaction with the multifunctional receptor αIIbβ3.Presented in part at the European Platelet Group Meeting, Erfurt, Germany, May 1996